2007
DOI: 10.1159/000102909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoxetine Alone and in Combination with Sildenafil in Patients with Premature Ejaculation

Abstract: Introduction: The aim of this study was to compare the efficacy of fluoxetine alone and combined with sildenafil in patients complaining of premature ejaculation. Patients and Methods: Ninety-one married potent men, 21–43 years old, with premature ejaculation but without any obvious organic cause were enrolled. Pretreatment evaluation included history, physical examination, and self-administration of the International Index of Erectile Function questionnaire. The patients were randomly divided into two groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 32 publications
2
47
0
1
Order By: Relevance
“…However, many patients, might not respond adequately to SSRIs, particularly those with erectile dysfunction(ED), likely because PE and ED are associated with each other 4,6 .Several recent studies have investigated the role of phosphodiesterase type 5(PDE-5) inhibitors, which are the first-line treatment for ED, reporting efficacy in the treatment of PE in the absence ofED [7][8] . It is noteworthy that PDE-5 inhibitors do not pharmacokinetically interact with SSRIs, and the combination of both is well tolerated 9 .In addition, efficacy and safety regarding the combination of PDE-5 inhibitors and SSRIs versus PDE-5 inhibitors or SSRIs monotherapy have also been investigated in the past decade [10][11][12][13] . A previous review has focused on this topic and suggested that combination therapy may be propitious to those who fail SSRI monotherapy or have concomitant ED and that it should not be the first-line M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 2 treatment for PE because of the adverse drug reactions 14 .…”
mentioning
confidence: 99%
“…However, many patients, might not respond adequately to SSRIs, particularly those with erectile dysfunction(ED), likely because PE and ED are associated with each other 4,6 .Several recent studies have investigated the role of phosphodiesterase type 5(PDE-5) inhibitors, which are the first-line treatment for ED, reporting efficacy in the treatment of PE in the absence ofED [7][8] . It is noteworthy that PDE-5 inhibitors do not pharmacokinetically interact with SSRIs, and the combination of both is well tolerated 9 .In addition, efficacy and safety regarding the combination of PDE-5 inhibitors and SSRIs versus PDE-5 inhibitors or SSRIs monotherapy have also been investigated in the past decade [10][11][12][13] . A previous review has focused on this topic and suggested that combination therapy may be propitious to those who fail SSRI monotherapy or have concomitant ED and that it should not be the first-line M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 2 treatment for PE because of the adverse drug reactions 14 .…”
mentioning
confidence: 99%
“…39,55,139,[142][143][144][145] Among these trials the dose was 50 mg or greater, administered a few hours preintercourse. Sildenafil was combined with fluoxetine in one trial 139 and with behavioural therapy in another, 143 i.e. there was no sildenafil-only arm in these two trials.…”
Section: 120mentioning
confidence: 99%
“…One RCT 55 that evaluated sildenafil and EMLA cream did not assess IELT. Post-treatment IELT data were available for one RCT assessing sildenafil and fluoxetine; 139 however, no variance estimates or p-values were reported. In one RCT assessing tadalafil and fluoxetine, 101 no IELT data were reported.…”
Section: Assessment Of Effectiveness: Phosphodiesterase-5 Inhibitors mentioning
confidence: 99%
“…On the other hand, some research suggested that phosphodiesterase type 5 (PDE-5) inhibitors such as sildenafil also had efficacy in the treatment of PE [9,[24][25][26]. Hosseini et al chose 91 patients with PE who were given 20 mg fluoxetine daily or plus 50 mg sildenafil as needed [26].…”
Section: Sertraline (N=53)mentioning
confidence: 99%